Identifikasi Bakteri Patogen Escherichia coli dan Salmonella spp. pada Rectal Swab Penjamah Makanan Rumah Sakit Di Yogyakarta - Nur Ahmad Rudin; Naufal Ghozi Aditya Perdana; Ninda Nur Amalia (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Microbial disease is an important health problem in Indonesia. Microbial diseases are often related to food sanitation, such as diarrhea, vomiting, typhus, gastrointestinal infections that caused by high levels microbial contamination in food served by various food providers. Pathogenic bacteria that often cause disease in humans are Salmonella spp. which causes typhus, and Escherichia coli which causes gastrointestinal infections, diarrhea, and meningitis. Analysis of pathogenic microbes is important to determine the types species of microbes that cause disease so the diseases that caused by pathogenic microbes in the community can be anticipated and handled appropriately. This study aims to determine the presence of pathogenic bacteria E. coli and Salmonella spp. on food handler rectal swab of hospital in Yogyakarta. The research was carried out by identification of bacteria with biochemical tests using BBL Crystal and pathogenicity test with E. coli antisera test. The results showed that pathogenic E. coli found in food handlers rectal swab of RS2004 and RS2005, and nonpathogenic E. coli found in RS2001, RS2002, dan RS2003. Salmonella spp. is not found in food handlers rectal swab of hospital in Yogyakarta.